2020
DOI: 10.1002/smll.201905055
|View full text |Cite
|
Sign up to set email alerts
|

Recreating Physiological Environments In Vitro: Design Rules for Microfluidic‐Based Vascularized Tissue Constructs

Abstract: Vascularization of engineered tissue constructs remains one of the greatest unmet challenges to mimicking the native tissue microenvironment in vitro. The main obstacle is recapitulating the complexity of the physiological environment while providing simplicity in operation and manipulation of the model. Microfluidic technology has emerged as a promising tool that enables perfusion of the tissue constructs through engineered vasculatures and precise control of the vascular microenvironment cues in vitro. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 139 publications
(246 reference statements)
0
28
0
Order By: Relevance
“…Unsurprisingly, some reports incorporate an endothelium owing to its inherent importance in tissue‐specific microenvironments (reviewed in refs. [ 10–14 ] ). In these reports, three methods of vascularizing MPSs are most common: 1) sacrificial molding of hollow lumens that are coated with ECs; 2) seeding of ECs on extracellular matrix (ECM) protein coated, rectangular polydimethylsiloxane (PDMS) microchannels; and 3) self‐assembly of microvessels within ECM‐like biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, some reports incorporate an endothelium owing to its inherent importance in tissue‐specific microenvironments (reviewed in refs. [ 10–14 ] ). In these reports, three methods of vascularizing MPSs are most common: 1) sacrificial molding of hollow lumens that are coated with ECs; 2) seeding of ECs on extracellular matrix (ECM) protein coated, rectangular polydimethylsiloxane (PDMS) microchannels; and 3) self‐assembly of microvessels within ECM‐like biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Vascularization of OOAC models offers a way to increase physiological relevance via a specific barrier and transport functionalities, as well as interstitial flow modeling, specialized cell-cell interactions, metastatic models, inflammatory models, and drug-or chemical-mediated toxicity models. Various forms of vascularization have been implemented thus far-from separate endothelial cell-lined fluidic supply channels over bioprinted models to specialized angiogenesis chips [43,[70][71][72][73]. Herland et al [19] recently demonstrated quantitative pharmacokinetic responses to orally administered nicotine and intravenously injected cisplatin inside their interconnected, vascularized organ chips that had been perfused using a common blood surrogate [19].…”
Section: Vascularization and Universal Culture Mediamentioning
confidence: 99%
“…We know that biotensegrity bases its foundations on the previous architectural model, with rigid and pre-stressed structures (bones and muscles); we know that the cell has been equated with this biological vision but, body fluids have not been taken into sufficient consideration [3]. We know that the presence of fluids is fundamental for the growth and survival of cells, as well as for the maintenance of the shape and function of tissues and organs [37][38][39]. In addition, the temperature itself within the different cellular fluid compartments is not homogeneous [40].…”
Section: Need For a New Fascial Modelmentioning
confidence: 99%